2019
DOI: 10.1021/acsomega.8b03156
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Large-Scale STEM Outreach Efficacy with a Consistent Theme: Thermodynamics for Elementary School Students

Abstract: A biannual chemistry demonstration-based show named “Energy and U” was created to extend the general outreach themes of science, technology, engineering, and mathematics (STEM) fields and a college education with a specific goal: to teach the first law of thermodynamics to elementary school students. The effectiveness of the program was analyzed using a clicker survey system for over 12 000 visiting students. The fraction of the students that correctly answered the question “Is it possible to create energy?” i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Furthermore, in terms of enhancing chemical safety education, safety moments are not limited to graduate level research; they have also been successfully incorporated into large K−12 informal outreach events at the University of Minnesota. 18,19 This model aligns with broader endeavors of infusing safety information competency in students at all ages 20 and can be reproduced by chemical educators in similar outreach efforts.…”
Section: ■ Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Furthermore, in terms of enhancing chemical safety education, safety moments are not limited to graduate level research; they have also been successfully incorporated into large K−12 informal outreach events at the University of Minnesota. 18,19 This model aligns with broader endeavors of infusing safety information competency in students at all ages 20 and can be reproduced by chemical educators in similar outreach efforts.…”
Section: ■ Introductionmentioning
confidence: 72%
“…Chemical safety is highly valued by all the principal investigators, experienced graduate students, and postdocs I have worked with; as initiated by the principal investigators during my time at the University of Minnesota and The University of Chicago, incorporating safety moments into our limited research group meeting time was one way that leadership showed that chemical safety is highly valued. Furthermore, in terms of enhancing chemical safety education, safety moments are not limited to graduate level research; they have also been successfully incorporated into large K–12 informal outreach events at the University of Minnesota. , This model aligns with broader endeavors of infusing safety information competency in students at all ages and can be reproduced by chemical educators in similar outreach efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Student survey responses revealed a recall of specific STEM facts learned at the STEM Days, as well as recollection of the unique STEM activities they engaged in. Previous researchers similarly reported learning gains by K-12 students following STEM outreach (Vollbrecht et al, 2019;DeWilde et al, 2019). Students' feedback responses also indicated that the STEM Day generated an interest in STEM professions.…”
Section: Discussionmentioning
confidence: 75%
“…Developing more positive attitudes toward science is hypothesized to encourage future study in that field, increase science literacy, and, ultimately inspire youth to pursue scientific careers and build a skilled STEM workforce. Encouraged by the NSF and other organizations, the creation of outreach activities focused on STEM has thus increased across sub-disciplines, including the activities and programs recently disseminated in this journal and others. Yet, how scientists and schools can best organize and perform such outreach activities so as to have maximum impact on students is not yet fully established. The parameters influencing students’ attitudes toward, interest in, and motivation to continue studying science are complex and remain an active area of educational research.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters influencing students’ attitudes toward, interest in, and motivation to continue studying science are complex and remain an active area of educational research. Excellent reviews have recently been published on the subject. ,, Unfortunately, few studies in chemistry ,, or other STEM disciplines , have assessed quantitatively the impact of individual outreach activities on students’ attitudes toward science. Nonetheless, these studies have identified some of the characteristics of successful programs that lead to greater positive changes in attitude toward STEM.…”
Section: Introductionmentioning
confidence: 99%